Modified reinforced concrete proportioning method
By optimizing the ratio of cementitious materials and selecting suitable aggregates, adding fly ash, waste section burning materials and polypropylene fibers, the problems of insufficient strength, poor durability and low crack resistance of traditional concrete are solved, and concrete with high strength, durability and crack resistance are achieved.
Patent Information
- Application Number
- CN202411887848.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
When traditional concrete faces the new requirements of modern construction projects, it lacks strength, poor durability and low crack resistance, making it difficult to meet the needs of large buildings and high-strength structures.
By optimizing the ratio of cementitious materials such as cement, mineral powder, slag powder, and reasonably selecting aggregates with hard texture and good grades, adding fly ash, waste section burning materials and polypropylene fibers, the microstructure and crack resistance of concrete are improved.
It improves the compressive, flexural strength and durability of concrete, enhances the permeability, frost resistance and corrosion resistance, extends the service life of the structure, and effectively improves crack resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete preparation, and in particular relates to a modified and reinforced concrete proportioning method. Background Art
[0002] With the acceleration of urbanization and the continuous advancement of construction technology, modern construction projects are showing a trend of diversification, large-scale and complexity. Large-scale infrastructure construction such as bridges, tunnels, high-rise buildings, etc. are constantly emerging, and these projects have put forward higher requirements on the performance of concrete. In terms of strength, concrete is required to have higher compressive and flexural strength to ensure the safety and stability of the structure and to be able to withstand greater loads and stresses. In terms of durability, concrete structures often face harsh environmental conditions.
[0003] In the prior art, although traditional concrete is widely used in construction projects, it gradually reveals its limitations when facing the new requirements of modern construction projects. The proportion of traditional concrete usually uses cement as the main cementitious material, supplemented by aggregates such as sand and stone. Its performance is limited to a certain extent by the quality and proportion of raw materials. In terms of strength, although the strength of concrete can be improved by increasing the amount of cement, it will also bring problems such as excessive hydration heat and large shrinkage, which will affect the durability and crack resistance of concrete. In terms of durability, the microstructure of traditional concrete is relatively loose and has a high porosity, which is easy to become a channel for water and harmful media to penetrate, thereby reducing its impermeability and corrosion resistance. In addition, traditional concrete also has deficiencies in frost resistance. Under the action of freeze-thaw cycles, it is easy to have surface peeling and internal structure damage, which affects the service life of concrete structures. In terms of crack resistance, traditional concrete is prone to cracks when subjected to stress due to its large brittleness. Especially in large-volume concrete projects, the crack problem is more prominent, which seriously affects the safety and durability of concrete structures. Summary of the invention
[0004] The purpose of the present invention is to provide a modified reinforced concrete mix method to solve the problems raised in the above background technology.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: the modified reinforced concrete mix ratio, by weight, includes 160-200 parts of cement; 90-120 parts of mineral powder; 50-70 parts of fly ash; 25-40 parts of waste section burnt material; 6-20 parts of admixture; 170-190 parts of slurry water; 36-85 parts of aggregate; 90-110 parts of fiber; 485-520 parts of stone chips; 1050-1100 parts of crushed stone; 30-75 parts of slag powder; 60-85 parts of mountain sand; and 55-105 parts of river sand.
[0006] In parts by weight, it includes 180 parts of cement; 110 parts of mineral powder; 55 parts of fly ash; 30 parts of waste burnt materials; 12 parts of admixture; 176 parts of slurry water; 65 parts of aggregate; 96 parts of fiber; 510 parts of stone chips; 1080 parts of crushed stone; 60 parts of slag powder; 75 parts of mountain sand; and 85 parts of river sand.
[0007] The fiber is made of polypropylene.
[0008] The crushed stone and mountain sand should be hard, well-graded and free of impurities.
[0009] The fibers meet relevant quality standards of the building materials industry and are surface treated to enhance adhesion to the cement matrix.
[0010] The slag powder is S95 grade slag powder.
[0011] The modified reinforced concrete mix ratio method specifically comprises the following steps:
[0012] S1. Pour the mineral powder, fly ash, waste burnt material, aggregate, stone chips, crushed stone, slag powder, mountain sand and river sand into the mixer in proportion, and dry mix for 5-7 minutes to mix the required materials;
[0013] S2. Pour cement into the mixer and continue stirring for 3 minutes;
[0014] S3, dissolving the admixture and the fiber in water to form an admixture solution;
[0015] S4. While the mixer is rotating continuously, pour the additional solution formed by the admixture and the fiber into the slurry water at the same time, allow the additional solution and the slurry water to be gradually poured into the interior of the mixer, and continue stirring for 6-8 minutes until the concrete is stirred evenly to form a modified and enhanced concrete.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) By optimizing the ratio of cement, mineral powder, slag powder and other cementitious materials, and rationally selecting hard and well-graded aggregates, the concrete has a high strength that can meet the requirements of large-scale buildings and high-strength structures;
[0018] (2) The addition of fly ash, mineral powder and slag powder improves the microstructure of concrete and increases its density, thereby enhancing its impermeability, frost resistance and corrosion resistance, and extending the service life of the concrete structure; the use of waste segment burners also helps to improve durability to a certain extent, while realizing the resource utilization of waste;
[0019] (3) The addition of polypropylene fibers effectively improves the crack resistance of concrete, prevents the generation and development of cracks, and improves the integrity and toughness of concrete. It is particularly suitable for projects with high requirements for crack resistance, such as large-volume concrete structures and areas susceptible to temperature stress. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] The invention provides a modified reinforced concrete mix ratio, which comprises, by weight, 160-200 parts of cement; 90-120 parts of mineral powder; 50-70 parts of fly ash; 25-40 parts of waste section burnt materials; 6-20 parts of admixture; 170-190 parts of slurry water; 36-85 parts of aggregate; 90-110 parts of fiber; 485-520 parts of stone chips; 1050-1100 parts of crushed stone; 30-75 parts of slag powder; 60-85 parts of mountain sand; and 55-105 parts of river sand.
[0022] In parts by weight, it includes 180 parts of cement; 110 parts of mineral powder; 55 parts of fly ash; 30 parts of waste burnt materials; 12 parts of admixture; 176 parts of slurry water; 65 parts of aggregate; 96 parts of fiber; 510 parts of stone chips; 1080 parts of crushed stone; 60 parts of slag powder; 75 parts of mountain sand; and 85 parts of river sand.
[0023] Cement: 160-200 parts, preferably 180 parts; cement is the main cementitious material of concrete, providing strength and adhesion to concrete;
[0024] Mineral powder: 90-120 parts, preferably 110 parts; mineral powder can improve the microstructure of concrete, increase its density and strength, and has a certain activity and can react with cement hydration products;
[0025] Fly ash: 50-70 parts, preferably 55 parts; fly ash has a ball effect, which can improve the workability of concrete and increase its later strength and durability;
[0026] Waste segment burning material: 25-40 parts, preferably 30 parts; using the waste as raw material after segment burning can not only realize the recycling of waste, but also improve the performance of concrete to a certain extent and reduce costs;
[0027] Admixture: 6-20 parts, preferably 12 parts; admixture can adjust the performance of concrete, such as improving fluidity, enhancing durability, etc., and reasonable allocation is carried out according to different types and functions of admixture;
[0028] Slurry: 170-190 parts, preferably 176 parts; Slurry plays the role of filling and hydration reaction in concrete, participates in the hydration process of cement, and affects the strength and working performance of concrete;
[0029] Aggregate: 36-85 parts, preferably 65 parts; Aggregate is the main component of concrete and plays a role in skeleton support. Its quality and gradation have an important impact on the strength and durability of concrete;
[0030] Fiber: 90-110 parts, preferably 96 parts, made of polypropylene; polypropylene fiber can effectively improve the crack resistance of concrete, prevent the generation and development of cracks, and enhance the integrity and toughness of concrete;
[0031] Stone chips: 485-520 parts, preferably 510 parts; stone chips can fill the gaps between aggregates, making the concrete more compact and improving the strength and stability of the concrete;
[0032] Crushed stone: 1050-1100 parts, preferably 1080 parts; Crushed stone with hard texture, good gradation and no impurities can provide good strength support for concrete, ensuring the compressive strength and durability of concrete;
[0033] Slag powder: 30-75 parts, preferably 60 parts, which is S95 grade slag powder. Slag powder has high activity and can undergo secondary hydration reaction with cement hydration products to further improve the strength and durability of concrete;
[0034] Mountain sand: 60-85 parts, preferably 75 parts; as a kind of natural sand, mountain sand can work synergistically with other aggregates to improve the performance of concrete under reasonable grading and quality control;
[0035] River sand: 55-105 parts, preferably 85 parts; river sand can also provide good particle grading and filling for concrete, and cooperate with other raw materials to improve the working performance and strength of concrete;
[0036] The fiber is made of polypropylene.
[0037] The crushed stone and mountain sand should be hard, well-graded, and free of impurities to ensure the strength and durability of the concrete. Good grading can make the aggregates fill each other, reduce the void ratio, and improve the density of the concrete.
[0038] The fibers meet relevant quality standards of the building materials industry, and the surface is treated to enhance adhesion with the cement matrix, which ensures that the fibers can better play a reinforcing role in concrete and improve the crack resistance and integrity of the concrete.
[0039] The slag powder is S95 grade slag powder.
[0040] The application of waste segment fuel realizes the reuse of waste, reduces the consumption of natural resources, reduces the pollution of waste to the environment, and is in line with the concept of sustainable development.
[0041] The modified reinforced concrete mix ratio method specifically comprises the following steps:
[0042] S1. Pour the mineral powder, fly ash, waste burnt material, aggregate, stone chips, crushed stone, slag powder, mountain sand and river sand into the mixer in proportion, and dry mix for 5-7 minutes to mix the required materials;
[0043] S2. Pour cement into the mixer and continue stirring for 3 minutes;
[0044] S3, dissolving the admixture and the fiber in water to form an admixture solution;
[0045] S4. While the mixer is rotating continuously, pour the additional solution formed by the admixture and the fiber into the slurry water at the same time, allow the additional solution and the slurry water to be gradually poured into the interior of the mixer, and continue stirring for 6-8 minutes until the concrete is stirred evenly to form a modified and enhanced concrete.
[0046] Mechanical properties test:
[0047] Compressive strength test: For cubic compressive strength specimens cured for 7 days, 28 days and 90 days, compressive strength tests were carried out using a pressure testing machine according to standard test methods.
[0048] Flexural strength test: For the flexural strength specimens cured for 28 days and 90 days, a three-point bending test was carried out on a flexural testing machine to determine the flexural strength.
[0049] Durability test:
[0050] Permeability test: For the durability test specimens that have been cured for 28 days, a permeability test is carried out using the step-by-step pressurization method, and the water pressure value when water seepage occurs in the specimens is recorded.
[0051] Freeze-thaw resistance test: The durability test specimens cured for 28 days are subjected to freeze-thaw cycle test. The mass loss and relative dynamic modulus change of the specimens are checked after every 25 cycles. The test is carried out until the relative dynamic modulus of the specimen drops below 60% or the mass loss rate exceeds 5%.
[0052] Mechanical properties results:
[0053] The compressive strength comparison test results of the concrete prepared by the mix ratio method of the present invention and the traditional concrete are shown in Table 1 below:
[0054] Table 1 is a table showing the compressive strength comparison test results of the concrete prepared by the present invention and the traditional concrete.
[0055]
[0056] The compressive strength of traditional concrete at 7 days, 28 days and 90 days is 30MPa, 40MPa and 50MPa respectively.
[0057] The compressive strength of the concrete of the present invention at 7 days, 28 days and 90 days is 45 MPa, 70 MPa and 85 MPa respectively.
[0058] The comparative test results of the flexural strength of the concrete prepared by the mix ratio method of the present invention and the traditional concrete are shown in Table 2 below:
[0059] Table 2 is a table showing the comparative test results of the flexural strength of the concrete prepared by the present invention and the traditional concrete.
[0060] time 28 days 90 days Traditional concrete 5MPa 6MPa Concrete of the present invention 9MPa 12MPa
[0061] The flexural strength of traditional concrete at 28 days and 90 days is 5MPa and 6MPa respectively.
[0062] The flexural strength of the concrete of the present invention at 28 days and 90 days is 9 MPa and 12 MPa respectively.
[0063] Durability Results:
[0064] The results of the comparative test on the impermeability of the concrete prepared by the mixing method of the present invention and the traditional concrete are shown in Table 3 below:
[0065] Table 3 is a table showing the results of the experimental comparison of the impermeability of the concrete prepared by the present invention and the traditional concrete.
[0066] Impermeability Traditional concrete 0.8MPa Concrete of the present invention 2.0MPa
[0067] Traditional concrete starts to seep water when the water pressure reaches 0.8MPa;
[0068] In the anti-seepage test, the concrete of the present invention can withstand a water pressure value of 2.0 MPa or more before water seepage occurs.
[0069] The results of the freeze-thaw resistance comparison test of the concrete prepared by the mixing method of the present invention and the traditional concrete are shown in Table 4 below:
[0070] Table 4 is a table showing the results of a comparative experiment on the freeze-thaw resistance of the concrete prepared by the present invention and the traditional concrete.
[0071] frequency Loss Rate Traditional concrete 150 times 5% Concrete of the present invention 300 times 2%
[0072] After 150 freeze-thaw cycles, the relative dynamic modulus of traditional concrete drops below 60% and the mass loss rate reaches 5%.
[0073] After 300 freeze-thaw cycles, the relative dynamic elastic modulus of the concrete of the present invention is still maintained at more than 80%, and the mass loss rate is less than 2%.
[0074] Processing of modified and reinforced concrete:
[0075] After accurately weighing the mineral powder, fly ash, waste burnt material, aggregate, stone chips, crushed stone, slag powder, mountain sand and river sand according to the calculated weight, pour them into the mixer for dry mixing, turn on the mixer, set the mixing time to 6 minutes, and make all kinds of materials fully mixed in a dry state;
[0076] After the dry mixing is completed, slowly pour the cement into the mixer according to the calculated weight and continue stirring for 3 minutes to ensure that the cement and other materials are evenly mixed to form a relatively uniform mixture;
[0077] During the stirring process, the admixture and the fiber are dissolved in water in a prescribed ratio and stirred evenly to form an admixture solution;
[0078] Then, while the mixer is rotating, slowly pour the additional solution formed by the admixture and fiber into the mixer together with the slurry, and continue stirring for 7 minutes. During this process, pay attention to the mixing state of the concrete to ensure that the additional solution and slurry are evenly dispersed in the concrete, so that the concrete is evenly mixed to achieve good working performance and modification and enhancement effects.
[0079] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. Modified reinforced concrete mix, characterized in that: By weight, it includes 160-200 parts of cement; 90-120 parts of mineral powder; 50-70 parts of fly ash; 25-40 parts of waste section burning material; and 6-20 parts of admixture. 170-190 parts of slurry water; 36-85 parts of aggregate; 90-110 parts of fiber; 485-520 parts of stone chips; 1050-1100 parts of crushed stone; 30-75 parts of slag powder; 60-85 parts of mountain sand; 55-105 parts of river sand.
2. The modified reinforced concrete mix according to claim 1, characterized in that: By weight, it includes 180 parts of cement; 110 parts of mineral powder; 55 parts of fly ash; 30 parts of waste section burning material; and 12 parts of admixture; 176 parts of slurry; 65 parts of aggregate; 96 parts of fiber; 510 parts of stone chips; 1080 parts of crushed stone; 60 parts of slag powder; 75 parts of mountain sand; 85 parts of river sand.
3. The modified reinforced concrete mix according to claim 1, characterized in that: The fiber is made of polypropylene.
4. The modified reinforced concrete mix according to claim 1, characterized in that: The crushed stone and mountain sand should be hard, well-graded and free of impurities.
5. The modified reinforced concrete mix according to claim 1, characterized in that: The fibers meet relevant quality standards of the building materials industry and are surface treated to enhance adhesion to the cement matrix.
6. The modified reinforced concrete mix according to claim 1, characterized in that: The slag powder is S95 grade slag powder.
7. A modified reinforced concrete mix method according to any one of claims 1 to 6, characterized in that: The specific steps include: S1. Pour the mineral powder, fly ash, waste burnt material, aggregate, stone chips, crushed stone, slag powder, mountain sand and river sand into the mixer in proportion, and dry mix for 5-7 minutes to mix the required materials; S2. Pour cement into the mixer and continue stirring for 3 minutes; S3, dissolving the admixture and the fiber in water to form an admixture solution; S4. While the mixer is rotating, pour the additive solution formed by the additive and fiber into the Add slurry, allow the added solution and slurry to gradually pour into the mixer, and continue stirring for 6-8 minutes. Until the concrete is mixed evenly to form modified and enhanced concrete.